2005
DOI: 10.1021/la047464l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of α-Lactalbumin on the Phase Behavior of AOT−Brine−Isooctane Mixtures:  Role of Charge Interactions

Abstract: We have found that both electrostatic and hydrophobic interactions are involved in the ability of the protein alpha-lactalbumin (alpha-LA) to affect the self-assembly of the anionic surfactant sodium bis(ethylhexyl) sulfosuccinate (AOT, 3.5 wt %) in equivolume mixtures of organic and aqueous solutions. The composition and size of AOT phase structures that form in the presence of 0.35 wt % protein were evaluated as a function of pH and ionic strength. In the absence of protein, AOT forms water-in-oil microemuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 59 publications
3
14
0
Order By: Relevance
“…For isooctane, the peak at 1.1 ppm was used, whereas for AOT, peaks at 1.2 and 3.9 ppm were used for the aqueous and organic phase concentrations, respectively. Optical properties were observed using a polarized light microscope (Nikon Laposhot 2A) . Samples were contained in glass capillaries used for X-ray scattering measurements and directly placed on the microscope stage to be observed.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…For isooctane, the peak at 1.1 ppm was used, whereas for AOT, peaks at 1.2 and 3.9 ppm were used for the aqueous and organic phase concentrations, respectively. Optical properties were observed using a polarized light microscope (Nikon Laposhot 2A) . Samples were contained in glass capillaries used for X-ray scattering measurements and directly placed on the microscope stage to be observed.…”
Section: Methodsmentioning
confidence: 99%
“…Small angle X-ray scattering from these aqueous phases suggested that these structures were small oil-in-water microemulsion droplets . Other studies indicated that conditions of pH and ionic strength had a strong influence on the AOT phase behavior modifications induced by αLA but did not obtain detailed information on the size, shape, or interparticle interactions of the resulting phase structures.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations